2007
DOI: 10.1089/hum.2006.107
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Therapeutic Efficacy of an Oncolytic Herpes Simplex Virus Type 1 Mutant Expressing ICP34.5 Under the Transcriptional Control ofmusashi1Promoter in the Treatment of Malignant Glioma

Abstract: Although second-generation replication-conditional herpes simplex virus type 1 (HSV-1) vectors defective for both ribonucleotide reductase (RR) and the virulence factor gamma(1)34.5 have been proven safe through a number of animal experiments and clinical trials, their therapeutic efficacy was also markedly reduced. To overcome this situation, we concentrated on the use of a tumor-specific promoter in this study, to express ICP34.5 selectively in malignant glioma cells. As a molecular marker for malignant glio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…(ii) Expression of inhibitors of PKR-mediated protein shutoff from other viruses, such as HCMV TRS1 or IRS1 (52), or the ␥34.5 homologous domain from cellular MyD116 (GADD34) (4). (iii) Targeted expression of ␥34.5 in cancer cells; transcriptionally through the use of tumor specific promoters, such as glioma selective nestin and musashi1 (23,24), or translationally through the use of a picornavirus IRES (10). Here, we have chosen to examine a deletion of the ␥34.5 BBD that was reported not to affect phosphatase activity (47).…”
Section: Discussionmentioning
confidence: 99%
“…(ii) Expression of inhibitors of PKR-mediated protein shutoff from other viruses, such as HCMV TRS1 or IRS1 (52), or the ␥34.5 homologous domain from cellular MyD116 (GADD34) (4). (iii) Targeted expression of ␥34.5 in cancer cells; transcriptionally through the use of tumor specific promoters, such as glioma selective nestin and musashi1 (23,24), or translationally through the use of a picornavirus IRES (10). Here, we have chosen to examine a deletion of the ␥34.5 BBD that was reported not to affect phosphatase activity (47).…”
Section: Discussionmentioning
confidence: 99%
“…The G207 virus, with further deletion of its α47 gene and promoter gene of US11 gene, is deprived of its neovascularity inducing effect [2] (see above). Table 2 lists some ideas leading to the construction of new oncolytic herpesviruses [145,174,195,216]. Dying tumor cells engulfed by DCs form DC vaccines, inasmuch as mature DCs express tumor antigens not in a tolerogenic, but in an immunogenic manner.…”
Section: Herpesvirusesmentioning
confidence: 99%
“…A key issue in developing a safe and effective oncolytic virotherapy is the achievement of maximal killing of tumor cells while maintaining tumor specificity of viral targeting (13)(14)(15). We have recently shown that a replication-defective HSV-1 helper virus (CgalΔ3), lacking the essential ICP4 gene, became oncolytic in a tissue type-specific fashion when the ICP4 gene was provided by an amplicon expressing this gene under the regulation of a prostate-specific promoter, ARR 2 PB (16).…”
mentioning
confidence: 99%